Utterances of Conservation Value and Character Teacher and Student in Learning Interactions at Adiwiyata School (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
One form of communication which occurs in the realm of education is in a classroom. In conveying their utterances, teachers not only give information but also have certain intentions. Based on this case, the study aims to analyze the types of utterances of teachers and students who are conservation-minded in their learning interaction at Adiwiyata schools. The research design used was qualitative descriptive. The data was collected by observation method, followed by uninvolved conversation observation technique, recording and taking notes.Furthermore, the data were analyzed using a pragmatic equivalent method with the basic technique to sort the determinants. The results of the study included the utterances types of representative (values of inspiring and honest characters), directive (value of inspiring, humanist, caring and honest characters), expressive (value of innovative and humanist characters), commissive (value of fair character), and declarative (value of inspiring, fair, caring and sportsmanlike characters). The results of this study provide theoretical and practical advantages. Theoretically, this study can find the types of utterances of conservation teachers and students in learning interactions at the Adiwiyata school. The practical advantage of this study is that teachers can use conservation-oriented utterances in conducting their learning interactions